Role of S. V. Korolenko in Evacuation of the Poltava Literary and Memorial Museum of V. G. Korolenko to Sverdlovsk in 1941 - A. S. Mokhov (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the problem of the evacuation of cultural values during the Great Patriotic War. The relevance of the research is due to the fact that in historiography insufficient attention is paid to the salvation of the treasures of provincial museums in 1941—1942. The question is raised about the lack of a unified plan for the evacuation of museum collections from the western regions of the USSR in the initial period of the war. The novelty of the research is in the introduction into scientific circulation of a unique document — a report on the evacuation of the literary and memorial museum of V. G. Korolenko from Poltava to Sverdlovsk. The question of the history of the creation of the museum and its work in the pre-war period is considered. The authors dwell on the history of the creation of literary and memorial museums in the USSR in the 1920s-1930s. The composition of the archive of V.G.Korolenko is characterized. It is shown that the graduates of the higher female Bestuzhev courses played a significant role in this process. Particular attention is paid to the activities of the museum director, the writer’s eldest daughter, Sofya Vladimirovna Korolenko. It has been proven that she is credited with saving the museum collection from the front line. According to the authors, the history of the evacuation of cultural property during the war is a poorly studied issue, the solution of which depends on the publication of sources.